Identifikasi Penyakit Protozoa Terhadap Manusia - Lestari Amalia Putri; Ismi Khofifah Ardellia; Nabila Fitriana; Agresia Moy; Acivrida Mega Charisma (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
Protozoa is a microscopic, one-cell organism that belongs to the protista group. Some protozoa species are pathogenic and can cause a variety of serious diseases in humans, which are often spread through water, contaminated food, or vectors such as mosquitoes and flies. Diseases caused by protozoa, such as malaria, amebiasis, giardiasis, and leishmaniasis, have a significant impact on public health, especially in developing countries with poor sanitation and limited health systems. This research uses a method (literature review) with a keyword search for articles on protozoa disease against humans in the context of articles in Indonesia. Data collection techniques using search processes in Google Scholar Research results show that increased awareness, education, and training for medical personnel are also important to ensure that protozoa infections can be diagnosed and treated effectively, thus minimizing the impact of the disease on society. Overall, the study emphasizes the importance of sanitation, personal hygiene, health education, routine screening, and vector control to reduce the prevalence of intestinal protozoa infections and improve the health of people with weakened immunity